2009
DOI: 10.4162/nrp.2009.3.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taurine supplementation on bone mineral density in ovariectomized rats fed calcium deficient diet

Abstract: Taurine supplementation has been shown to have a beneficial effect on femur bone mineral content in ovariectomized rats. It therefore seemed desirable to find out whether the beneficial effect of taurine on ovariectomized rats fed calcium deficient diet could also be reproduced. Forty female Sprague-Dawley rats were divided into two groups. One group was OVX and the other group received sham operation (SHAM), and received either control diet or a taurine supplemented diet for 6 weeks. All rats were fed on calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 36 publications
3
4
0
Order By: Relevance
“…The results showed that the mean body weight in ovariecto- mized rats compared with the control group significantly increased. These results agree with previous studies that weight gain is caused by lack of hormonal correspond (1,14). It is well known that weight gain occurs in postmenopausal women.…”
Section: Discussionsupporting
confidence: 83%
“…The results showed that the mean body weight in ovariecto- mized rats compared with the control group significantly increased. These results agree with previous studies that weight gain is caused by lack of hormonal correspond (1,14). It is well known that weight gain occurs in postmenopausal women.…”
Section: Discussionsupporting
confidence: 83%
“…Body weight did not differ between Sham and Ovx groups (244 ± 2 g and 243 ± 5 g) at the beginning of study, but after four-month ovariectomy, body weight was higher for the Ovx group, by 1.26-fold, than the Sham group ( p = 0.0029) ( Figure 2 A). These results agree with earlier reports and it is believed that the increased body weight is due to hormonal deficiency in menopausal women and is linked to increased weight of particularly epididymal fat [ 27 , 28 , 29 ]. The mean liver weights in the Sham and Ovx groups did not differ (8.99 ± 0.27 g and 9.24 ± 0.71 g, respectively, p = 0.7468) ( Figure 2 B).…”
Section: Resultssupporting
confidence: 93%
“…The positive effect of Tau on bone metabolism and regeneration are reported in other studies. Mi-Ja Choi 37 showed the beneficial effect of Tau supplementation on femur bone mineral content. In another study, Park et al 38 reported collagen synthesis, tyrosine phosphorylation, and alkaline phosphatase activity stimulation in UMR-106 cells under treatment with Tau.…”
Section: Resultsmentioning
confidence: 99%